The scaling of hybrid method in solving unconstrained optimization method - Mustafa, Mamat; Puspa Liza, Ghazali; Mohd Asrul, Hery Ibrahim (Pushpa Publishing House, 2016)
In this paper, the solution of unconstrained optimization problems has been suggested by using scaling of BFGS-SD method. This method is globally convergent with inexact line searches for general convex functions. The number of iterations and CPU-time of this method has been compared with those of the original BFGS method. © 2016 Pushpa Publishing House, Allahabad, India.